Macronutrient and Micronutrient Analysis of Bilih Fish-Based Finger Food as a Local Food Innovation from West Sumatra to Support the Nutrition of Pregnant Women - Fadhil Acedya Adhyatmoko; Figo Dwi Cahyo; Dita Zahratul Fathny; Navila Samsa Volasoohy; Salma Nasira Rusdha; Zuhrah Taufiqa (International Journal of Health Engineering and Technology, 2026)
West Sumatra faces a nutritional paradox in which low birth weight prevalence (6.4%) coexists with high stunting rates (24.9%), indicating chronic maternal micronutrient deficiencies during pregnancy. This study aimed to develop a local food innovation in the form of bilih fish (Mystacoleucus padangensis)-based finger food and analyze its macronutrient and micronutrient content to support maternal nutrition. A descriptive observational design with laboratory analysis based on Indonesian National Standards (SNI) was used. The results showed that the bilih fish finger food had an energy density of 188.19 kcal/100 g, a crunchy texture, and minimal fishy aroma, making it suitable for pregnant women, including those with emesis gravidarum. The protein content reached 16.52 g/100 g, fulfilling approximately 55–80% of the additional daily protein requirements during pregnancy. Zinc content was 1.32 mg/100 g (13.22 mg/kg), higher than several other local food sources such as dadiah and eggs. In conclusion, bilih fish-based finger food has strong potential as a functional local food to address maternal micronutrient deficiencies and serve as a preventive strategy to reduce stunting risk in West Sumatra starting from the intrauterine period.